The Boma: They are what they eat - But what are we telling farmers to feed their animals? - International Livestock Research Institute (International Livestock Research Institute, 2021)
There have been over 22,000 studies on the best ways for farmers to feed their livestock. But how many have looked at whether farmers actually benefited? Jeremy Cherfas interviews Isabelle Baltenweck, leader of the Policies, Institutions and Livelihoods, about the differences and distances between livestock researchers and livestock farmers.